The Effect of University Openings on Local Human Capital Formation: Difference-in-Differences Evidence from Germany - Benedikt Siegler (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2012)
Between 1960 and 1979, 93 new universities opened in Germany. Using this large tertiary education expansion, I estimate the effect of a university opening on the probability of obtaining a university degree in the local population. I exploit the geographical variation in local university access in a difference-in-differences approach by comparing age cohorts in counties that were and were not affected by the opening. Results show that a new university increases the share of university graduates in a county by 8 to 10 percentage points. The effect seems to be mainly driven my females and immigrants.
Keywords: I23; I28; H75; 330; tertiary education; education expansion; difference-in-differences; natural experiment; new university opening; Hochschule; Regionale Inzidenz; Bildungsverhalten; Absolventen; Bildungsabschluss; Deutschland